Teaching concepts in ultrasound-guided regional anesthesia - Keßler, Jens; Hollmann, Markus W.; Stevens, Markus Florian (Current opinion in anaesthesiology, 2016)
Purpose of review Ultrasound-guided regional anesthesia is a challenging, complex skill and requires competence in teaching. The aim of this study was to review current literature on identification of education and learning of ultrasound-guided regional anesthesia and to summarize recent findings on teaching concepts. Recent findings Several teaching programs have been described and implemented into daily routine. Factors relevant to current practice are the knowledge of sonoanatomy, the acquisition of manual skills, the teaching ability, and the feedback given to the trainee. Simulation is a rapidly growing field and is supported by the development of phantoms. Needle visualization is one of the core competencies that is necessary for successful ultrasound-guided procedures and could be supported by technical developments in the future to improve teaching concepts. Summary Although a lot of key questions cannot be answered by the latest study results, some interesting findings were able to improve existing education programs. These results should be tailored to the individual need of a trainee, and the effects of improved training programs on patient safety and quality of care have to be investigated. The see one, do one, teach one approach is obsolete and should be abandoned.
Gesehen am 05.12.2017